Adult Vaccination Rates in the Mentally Ill Population: An Outpatient Improvement Project. (March 2020) - Miles, Leslie W.; Williams, Nathalia; Luthy, Karlen E.; Eden, Lacey
Background: Adults who suffer with severe and persistent mental illness (SPMI) rarely access medical care to receive preventive vaccines.Aims: To increase the rate of vaccines among the SPMI population in an outpatient community mental health center (CMHC).Methods: A review of the literature identified a gap between the general population and SPMI clients in receiving preventive vaccinations. An initial mixed-method convenience survey of SPMI clients ( n = 392) provided information on current vaccination status, demographics, beliefs, and interest in receiving vaccines. A vaccination program was developed to address identified barriers and increase vaccination rates. Postintervention data were collected through a mixed-method convenience survey of SPMI clients ( n = 60) who participated in immunizations clinics to evaluate client satisfaction. A partnership between the health department and CMHC was developed to deliver vaccines in a nontraditional site. Vaccines administered included annual influenza; hepatitis A; hepatitis B; herpes zoster; measles, mumps, and rubella; pneumococcal; and tetanus, diphtheria, and pertussis (Tdap).Results: More than 1, 000 vaccines were administered in the first 8 months, with a significant increase in vaccination rates over baseline for individual vaccines ranging from 18.75% to 83%. Postintervention survey results found a 95% satisfaction rate.Conclusions: Implementation of a vaccination program in a nontraditional site that facilitates access for SPMI clients can promote an overwhelming increase in the vaccination rates for this underserved population. Results suggest that the integration of mental health and CMHC services can have a profound positive effect on SPMI population health.